Solar lasers: Why not? - Küblböck, Michael; Will, Jonathan; Fattahi, Hanieh (APL Photonics, 2024)
In this paper, we investigate the role of solar laser technology as a pivotal element in advancing sustainable and renewable energy. We begin by examining its wide-ranging applications across diverse fields, including remote communication, energy storage through magnesium production, and space exploration and communication. We address the current challenges faced by solar laser technology, which include the necessity for miniaturization, operation at natural sunlight intensity without the need for concentrated power, and efficient energy conversion. These improvements are essential to elevate their operational performance, beam quality, and cost-effectiveness. The promising prospects of space-based solar-pumped lasers and their potential role in magnesium generation for a sustainable energy future highlight some of the vast application opportunities that this novel technology could offer.
CRIS-Team Scopus Importer:2024-06-14